Influence of precipitation and land use on flows in the Hydrographic Sub-Region Itacaiúnas (SRHI) (Research, Society and Development, 2021)
Over the last few years, the hydrographic basins have undergone substantial changes in their hydrological behavior as well as in the conditions of use and occupation of the soil due to economic activities. In this sense, the objective of this study is to analyze and characterize the effects of precipitation and land use and occupation on the flow of the Itacaiúnas Hydrographic Sub-Region (SRHI) between the periods 1988 to 2017. For this, information regarding the series flow and precipitation storms over a 30-year period were obtained from stations located in the region, which are available on the website of the National Water Agency (ANA). In addition, land use and occupation data from the MapBiomas project were also obtained for the same period of 30 years. Subsequently, correlations were made between rainfall and flow, as well as for land use and occupation and flow. With that, it was observed that the outflows had a close relationship with the precipitation however, the use of the land did not present expressive correlation with the dynamics of the flow in the region.